Scheduling of event-triggered controllers on a shared network - Cervin, A.; Henningsson, T. (2008 47th IEEE Conference on Decision and Control, 2008)
We consider a system where a number of independent, time-triggered or event-triggered control loops are closed over a shared communication network. Each plant is described by a first-order linear stochastic system. In the event-triggered case, a sensor at each plant frequently samples the output but attempts to communicate only when the magnitude of the output is above a threshold. Once access to the network has been gained, the network is busy for T seconds (corresponding to the communication delay from sensor to actuator), after which the control action is applied to the plant. Using numerical methods, we compute the minimum-variance control performance under various common MAC-protocols, including TDMA, FDMA, and CSMA (with random, dynamic-priority, or static-priority access). The results show that event-triggered control under CSMA gives the best performance throughout.